Responsible Research and Innovation Associated With Risk Communication and Public Engagement on Health Emergency Preparedness at the Local Level - Valentina Possenti; Barbara De Mei; Anna Kurchatova; Manfred Green; Kåre Harald Drager; Roberta Villa; Alberto d'Onofrio; Mitra Saadatian-Elahi; Vanessa Moore; Kjersti Brattekas; Pania Karnaki; Ariel Beresniak; et al. (Frontiers in Communication, 2022)
Responsible Research and Innovation (RRI) associated with public health emergency preparedness (PHEP) and response pose major challenges to the scientific community and civil society because a multistakeholder and interdisciplinary methodology is needed to foster public engagement. In 2017, within “Action plan on Science in Society related issues in Epidemics and Total pandemics”, twenty-three initiatives in eleven cities—Athens, Brussels, Bucharest, Dublin, Geneva, Haifa, Lyon, Milan, Oslo, Rome, and Sofia—represented effective opportunities for Mobilization and Mutual Learning on RRI issues in the matter of PHEP with different community-level groups. These experiences show that to effectively address a discourse on RRI-related issues in PHEP it is necessary to engage the local population and stakeholders, which is challenging because of needed competencies and resources. Under coronavirus disease 2019 (COVID-19) pandemic, we are proven that such a diversified multistakeholder engagement on RRI related to PHEP locally needs further elaboration and practical development.